Inadequate Flexibility and Resistance to Change Hindering Effectiveness of ERP System in Accounting - Sherzad Ramadhan; Kamil Ghanim Ahmed; Hassan Koutaini; Ma'moun W. Aridah; Fareeba Ahmed (European Scientific Journal, ESJ, 2020)
The Enterprise Management Planning (ERP) software applications allow companies to integrate key daily activities such as procurements, financial, production, human resources, and project activities and helps organizational stakeholders to facilitate efficient decision making based on integrated data from various departments. Many accountants have not been able to realize the effectiveness of the ERP system due to its inadequate flexibility to adapt to change and resistance among some accountants that use the system. This research aims at showing the role that the inadequate flexibility of the system plays in impeding the ERP software from guaranteeing effectiveness and depicts how resistance to change among different stakeholders in an organization hinders the effectiveness of the enterprise resource planning (ERP) system in accounting. It uses a qualitative research method entailing semi-structured interviews with multiple employees working in the accounts department in different organizations. The study revealed that many accountants are driven by fear of new technology, making them resist the ERP system. Participants also affirmed that ERP does not readily adapt to organizational changes in the accounting departments. The major limitation of this study is that it focused on a small sample population because of the limited funds to cater to many participants.